2022
DOI: 10.1002/srin.202200325
|View full text |Cite
|
Sign up to set email alerts
|

Recrystallization Behavior of Hot‐Rolled Microstructure with Texture Gradient and Texture of Final Sheet in Thin‐Gauge Electrical Steel

Abstract: The typical feature of hot‐rolled sheets exhibits strong inhomogeneity in microstructure and texture along the thickness direction, and the latter can be named as texture gradient. Herein, the recrystallization and grain growth behaviors of the hot‐rolled sheet in a thin‐gauge nonoriented electrical steel are investigated at different normalization temperatures. The origin and the growth behavior of the main recrystallization texture {114}<481> are revealed. The results show that the texture gradient in hot‐ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Therefore, the corresponding texture is weakened without significant changes, and it is also obviously different from the typical {114}<481> texture that appears at high‐temperature normalization annealing. [ 20 ] Furthermore, the uneven hot rolling process results in a significant microstructure disparity between the surface layer and the central layer. Consequently, during low‐temperature annealing and recrystallization, a substantial size discrepancy arises, forming a small number of near {100} grains larger than 100 μm.…”
Section: Results and Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the corresponding texture is weakened without significant changes, and it is also obviously different from the typical {114}<481> texture that appears at high‐temperature normalization annealing. [ 20 ] Furthermore, the uneven hot rolling process results in a significant microstructure disparity between the surface layer and the central layer. Consequently, during low‐temperature annealing and recrystallization, a substantial size discrepancy arises, forming a small number of near {100} grains larger than 100 μm.…”
Section: Results and Analysesmentioning
confidence: 99%
“…In a separate work, we carried out the experiment of heating and rolling the continuous casting slab directly at 900 and 1100 °C held for 10 min, and confirmed that the coarse and deformed ferrite could be obtained. [ 20 ] The described methodology and analysis provide valuable insights into the microstructure evolution during the industrial production of low‐grade electrical steels. The proposed approach of heating the columnar‐grained slab at 900 °C for 20 min, followed by further heating to 1100 °C for a holding time of 10–20 min before hot rolling, allows for a detailed examination of the structural changes.…”
Section: Discussionmentioning
confidence: 99%